Exploring Psychological Well-being of Indonesian Pre-service English Teachers as Non-native Speakers - Sya'idah, Ifa Maghfirotus; Rohmana, Wahyu Indah Mala (Universitas Muhammadiyah Metro, 2023)
This study examines the psychological well-being of Indonesian pre-service English teachers, considering non-native speakers during their teaching practice. Well-being is defined from eudaimonic and hedonic perspectives, emphasizing self-actualization, positive relationships, emotions, satisfaction, and happiness. Pre-service teachers face challenges in managing emotions, establishing student relationships, and language anxiety. Forty-eight Indonesian pre-service English teachers completed questionnaires, and 10 underwent in-depth semi-structured interviews. Findings revealed a high level of psychological well-being among the pre-service teachers, with positive scores in autonomy, environmental mastery, personal growth, self-acceptance, purpose in life, and positive relations. However, language anxiety impacted their confidence in English communication compared to native speakers. Significant transitions, professional domains, emotional intelligence, self-efficacy, and language anxiety were identified as factors influencing their well-being. Preparing pre-service teachers mentally, emotionally, and intellectually to handle teaching demands is crucial. Improving psychological well-being can enhance teaching performance and student outcomes. While specific to Indonesia, this study calls for further research in diverse educational settings to inform strategies for supporting pre-service teacher well-being.